Cortical bone thickness of the adult alveolar process - a retrospective CBCT study - Germec-Cakan Derya; Tozlu Murat; Ozdemir Fulya (Sciendo, 2014)
Objectives: To investigate and compare cortical bone thickness of the posterior alveolar process in adult patients presenting with skeletal Class I, II and III malocclusions.